C.D.S. III aniversario, 9 de septiembre : más firmes, más revolucionarios (CDS (Comite de Defensa Sandinista))
Red, white and black poster, with drawing depicting people performing a range of activities Poster advertising 3rd year since the formation of the CDS in Nicaragua PO-0174